The psy knowledge and the field of health: the circulation of psychoanalytic discourse in specialized journals (1946-1955) - Savio, Karina (2021)
In this article we analyze the different modes that psychoanalytic discourse adopted in Argentine society during the years in which Peronism held power, that is, between 1946-1955. For this, it has been considered the relationship established between this knowledge, at that time, novel, and the field of health. At the same time, the place occupied by the social dimension in this area and its articulation with psychoanalysis have been revealed. To this end, publications from various specialized journals related to psychiatry, pediatrics, mental hygiene, kinesiology, and occupational medicine have been reviewed. As a conceptual tool, we haveused the notion discursive object employed by discourse analysis. We have examined the senses that are constituted around the psychoanalytic object in these materials. Even though the link between this knowledge and Peronism has generally been relegated in research that traces its evolution in this country, in this work it has been shown that the object-knowledge psychoanalysis acquires in these years three different meanings: as questionable knowledge, as theoretical knowledge and as revolutionary knowledge. Likewise, the importance of the social dimension has been verified in some of the articles studied.